Selenium supplementation and insulin resistance in a randomized, clinical trial - Elizabeth Theresa Jacobs; Peter Lance; Lawrence J Mandarino; Nathan A Ellis; H-H Sherry Chow; Janet Foote; Jessica A Martinez; Chiu-Hsieh Paul Hsu; Ken Batai; Kathylynn Saboda; Patricia A Thompson (BMJ Open Diabetes Research & Care)
Objective While controversial, observational and randomized clinical trial data implicate the micronutrient selenium (Se) in the development of type 2 diabetes (T2D). The aim of this study was to test the hypothesis that Se supplementation adversely affects pancreatic β-cell function and insulin sensitivity.Research design and methods In a subset of 400 individuals participating in a randomized, placebo-controlled trial of Se at 200 µg/day for colorectal adenomatous polyps, fasting plasma glucose and insulin were measured before randomization and within 6 months of completing intervention. Change in the homeostasis model assessment-β cell function (HOMA2-%β) and insulin sensitivity (HOMA2-%S) were compared between arms. A subgroup of 175 (79 Se and 96 placebo) participants underwent a modified oral glucose tolerance test (mOGTT) at the end of intervention and change in glucose values was assessed.Results No statistically significant differences were observed for changes in HOMA2-%β or HOMA2-%S between those who received Se compared with placebo. After a mean of 2.9 years on study, mean HOMA2-%β values were 3.1±24.0 and 3.1±29.8 for the Se and placebo groups, respectively (p=0.99). For HOMA2-%S, the values were −0.5±223.2 and 80.9±1530.9 for the Se and placebo groups, respectively (p=1.00). Stratification by sex or age did not reveal any statistically significant effects on insulin sensitivity by treatment group. For mOGTT, mean baseline fasting blood glucose concentrations were significantly higher among participants in the placebo group compared with the Se group (96.6±14.6 and 92.3±12.0, respectively; p=0.04), a trend which remained through the 20 min assessment.Conclusions These findings do not support a significant adverse effect of daily Se supplementation with 200 µg/day of selenized yeast on β-cell function or insulin sensitivity as an explanation for previously reported associations between Se and T2D. Further clarification of longer term effects of Se is needed.Clinical trial registry NIH Clinical Trials.gov number NCT00078897.